2013
DOI: 10.1016/j.nuclphysb.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Gluon Regge trajectory at two loops from Lipatovʼs high energy effective action

Abstract: We present the derivation of the two-loop gluon Regge trajectory using Lipatov's high energy effective action and a direct evaluation of Feynman diagrams. Using a gauge invariant regularization of high energy divergences by deforming the light-cone vectors of the effective action, we determine the two-loop self-energy of the reggeized gluon, after computing the master integrals involved using the Mellin-Barnes representations technique. The self-energy is further matched to QCD through a recently proposed subt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…2. Determination of NLO corrections using this effective action approach has been addressed recently to a certain extent, through the explicit calculation of the NLO corrections to both quark [16] and gluon [17] induced forward jets (with associated radiation) as well as the determination of the gluon Regge trajectory up to 2 loops [18]. These previous applications have all in common that they are, at amplitude level, restricted to a color octet projection and, therefore, single reggeized gluon exchange.…”
Section: The High-energy Effective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Determination of NLO corrections using this effective action approach has been addressed recently to a certain extent, through the explicit calculation of the NLO corrections to both quark [16] and gluon [17] induced forward jets (with associated radiation) as well as the determination of the gluon Regge trajectory up to 2 loops [18]. These previous applications have all in common that they are, at amplitude level, restricted to a color octet projection and, therefore, single reggeized gluon exchange.…”
Section: The High-energy Effective Actionmentioning
confidence: 99%
“…The calculation of higher order corrections from the effective action approach [14] has been successfully explored by our group in recent years. In particular, both NLO impact factors for quark [16] and gluon induced forward jets [17] and the gluon Regge trajectory up to two loops [18] have been obtained making use of Lipatov's effective action and a set of supplementary calculational rules. In the following we will use this framework for the determination of the missing real NLO corrections which will be then combined at partonic level with the already known virtual corrections.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main advantages of Lipatov's high energy effective action is that it provides a gauge invariant factorization of QCD amplitudes in the high energy limit through introducing a new type of field, i.e., the Reggeized gluon. Using this effective action it has been possible to both reproduce and derive a number of next-to-leading order (NLO) results, most notable the calculation of NLO correction to forward jet production without [13,14] and with rapidity gap [15], the gluon Regge trajectory up to two loops [16], and the NLO kernel of the Bartels-KwiecinskiPraszalowicz evolution equation [17] (see also the review [18]); for the determination of NLO corrections for Reggeized quarks, see [19]. The description of scattering amplitudes for multiple Reggeized gluon exchange has also been studied by a number of authors; see, e.g., [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…He found that after this projection the dependence on the sign of vanishes and the vertices satisfy the desired properties of Bose symmetry and negative signature of the reggeon. It was checked that his recipe reproduced the QCD results for the gluon trajectory with one and two loops [14][15][16]. However, his prescription refers only to the induced vertices themselves and consequently to the amplitude with a single interaction of colliding particles and not to the one with several interactions as in our case.…”
Section: Discussionmentioning
confidence: 81%